Cd exposure-induced growth retardation involves in energy metabolism disorder of midgut tissues in the gypsy moth larvae. (November 2020) - Jiang, Dun; Zhou, Yantao; Tan, Mingtao; Zhang, Jie; Guo, Qingxi; Yan, Shanchun
Abstract: Cadmium, a common environmental contaminant in both terrestrial and aquatic ecosystems, presented a serious hazard to growth and development of phytophagous insects. For better understanding the toxicology of Cd exposure on phytophagous insects, the physiological and molecular mechanisms underlying the energy metabolism disorder in midgut tissue of gypsy moth larvae fed on Cd-amended artificial diets (3.248 or 44.473 mg Cd/kg fresh food) were investigated. Our results showed that compared with control, Cd exposure at both two levels triggered detriment effects on growth indexes, and with the increase of exposure concentrations, the adverse effects were significantly exacerbated. Larval growth and nutritional indexes (except approximate digestibility) showed a strong positive correlation, indicating that growth retardation in the gypsy moth larvae under Cd stress was tightly related to the food utilization. The key genes at mRNA level in glycolysis/gluconeogenesis, citrate cycle pathway and starch/sucrose metabolism pathway also presented a significant and positive correlation with growth indexes, once again demonstrating that energy metabolism was the key factor that controls the growth and development of the gypsy moth larvae under Cd stress. Antioxidant system collapse and oxidative damage, a chief cause of histopathological alterations in midgut tissue, consist of the physiological basis of energy metabolism disorder in Cd-treated gypsy moth larvae. Together, these results suggest that histopathological alterations or oxidative damage of tissue structure significant disturbed physiological functions of midgut tissue in gypsy moth larvae exposed to Cd stress, as reflected via food utilization or energy metabolism disorder, and eventually resulted in larval growth retardation. Graphical abstract: Image 1 Highlights: Cd-induced detrimental effects in gypsy moth larvae were assessed. Cd exposure disturbed the growth and development of gypsy moth larvae. Growth retardation involves in structure damage and dysfunction of midgut tissues. Abstract : Main finding: Cd exposure-induced growth retardation involves in energy metabolism disorder of midgut tissues in the gypsy moth larvae.